Life‐history traits and physiological limits of the alpine fly Drosophila nigrosparsa (Diptera: Drosophilidae): A comparative study. Issue 4 (17th January 2018) - Kinzner, Martin‐Carl; Krapf, Patrick; Nindl, Martina; Heussler, Carina; Eisenkölbl, Stephanie; Hoffmann, Ary A.; Seeber, Julia; Arthofer, Wolfgang; Schlick‐Steiner, Birgit C.; Steiner, Florian M.
Abstract: Interspecific variation in life‐history traits and physiological limits can be linked to the environmental conditions species experience, including climatic conditions. As alpine environments are particularly vulnerable under climate change, we focus on the montane‐alpine fly Drosophila nigrosparsa . Here, we characterized some of its life‐history traits and physiological limits and compared these with those of other drosophilids, namely Drosophila hydei, Drosophila melanogaster, and Drosophila obscura . We assayed oviposition rate, longevity, productivity, development time, larval competitiveness, starvation resistance, and heat and cold tolerance. Compared with the other species assayed, D. nigrosparsa is less fecund, relatively long‐living, starvation susceptible, cold adapted, and surprisingly well heat adapted. These life‐history characteristics provide insights into invertebrate adaptations to alpine conditions which may evolve under ongoing climate change. Abstract : Life‐history traits and physiological limits of the alpine fly Drosophila nigrosparsa were assayed in the laboratory and compared with those of four other Drosophila species. Drosophila nigrosparsa has relatively low fecundity, is long‐living, starvation susceptible, cold adapted, and surprisingly heat tolerant.